Penggunaan Metode Insya’ Muwajjah Sebagai Proses Pembelajaran Kitabah - Annisa Annisa; Dini Febria Arifina; Haidarul Gholib Al-Ghozi; Yuyun Jelita Jabat; Sahkholid Nasution (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
One of the four Arabic language skills is the ability to write, or what is called maharah al-kitabah. There are four categories of Arabic language skills, namely listening skills (maharah al-istima'), speaking skills (maharah al-kalam), reading skills (maharah al-qira'ah), and writing skills (maharah al-kitabah). Writing is an activity related to the thinking process and the ability to convey ideas through writing. Insya' muwajjah, or structured writing, is one method to improve the ability of maharah al-kitabah with a teaching method that asks students to write perfect sentences or essays with some direction and instructions from the teacher. This research was conducted with the aim of getting an answer to whether one of the insha' muwajjah learning methods could be an alternative for achieving success for a teacher in teaching one of the skills that is included in the most difficult level of other maharah. This research uses analysis that the author quotes from various secondary data, in the form of scientific journals, theses and internet media. From the results that we have collected from various previous sources, it shows that the insha' muwajjah method can be an alternative because the learning carried out starts from easy to difficult stages so that students' understanding can be evenly captured in learning until skills are formed.